Faktor-faktor yang Memengaruhi Transformasi Digital UMKM di Indonesia - Alyani, Ilma; Saptono, Imam Teguh; Jahroh, Siti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
Digital transformation is imperative for Micro, Small, and Medium Enterprises (MSMEs) to endure and thrive within the dynamic contemporary business environment. Despite the Indonesian government's digital transformation goals for MSMEs, the realization of this goal remains far. This study aims to identify the key factors influencing the digital transformation of Indonesian MSMEs. Drawing from extensive prior research, we investigate the impact of government support, community support, digital orientation, and digital capabilities on MSMEs' digital transformation, and its effect on financial performance. To achieve this, an online survey was disseminated, capturing responses from 324 participants, and the data was analyzed using the SmartPLS 4. This research found that government support, digital orientation, and digital capabilities significantly influence digital transformation. However, community support shows no significant impact. Furthermore, our research reveals a substantial positive correlation between digital transformation and improved financial performance in Indonesian MSMEs, highlighting the profound business benefits of embracing digitalization. These findings emphasize the need to strengthen internal factors as a critical driver for accelerating digital transformation in Indonesian MSMEs.